2005
DOI: 10.1159/000084833
|View full text |Cite
|
Sign up to set email alerts
|

Effect of School-Based Fluoride Varnish Programmes on Approximal Caries in Adolescents from Different Caries Risk Areas

Abstract: The aim was to evaluate, in a 3-year RCT study, school-based fluoride varnish programme on approximal caries incidence and approximal caries progression in 13- to 16-year-olds in high, medium and low caries risk areas on the Swedish west coast. Seven hundred and fifty-eight (89%) fulfilled the trial. Using a simple mobile unit, 2 dental nurses treated the adolescents with F varnish: (1) twice a year at 6-month intervals, (2) 3 times a year within 1 week, (3) 8 times per year during the semesters with 1-month i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(26 citation statements)
references
References 50 publications
0
21
2
2
Order By: Relevance
“…Most previous studies of BMI versus caries have only included cavities and fillings. In this investigation, however, initial approximal lesions, scored on bitewing radiographs, were included in the analyses, thereby providing a more complete picture of the total approximal caries situation, because up to 80–90% of decayed approximal surfaces are reported to be initial caries 17,26 .…”
Section: Discussionmentioning
confidence: 99%
“…Most previous studies of BMI versus caries have only included cavities and fillings. In this investigation, however, initial approximal lesions, scored on bitewing radiographs, were included in the analyses, thereby providing a more complete picture of the total approximal caries situation, because up to 80–90% of decayed approximal surfaces are reported to be initial caries 17,26 .…”
Section: Discussionmentioning
confidence: 99%
“…For example, in 11‐ to 12‐year olds, it has been shown that subjects with one approximal lesion or more have 2.5 times higher risk for new proximal caries lesions compared to those with a lower score 28 . An interesting approach to the problem is school‐based fluoride varnish treatments carried out every 6 months 29 . This outreach concept was proven successful, especially in young teenagers from a high‐caries community, and one of the reasons might have been that the children did not have to take own responsibility for the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…At present, the only thresholds that can be definitely identified as not appropriate are those that call for surgical treatment when caries is confined to enamel, due to the potential for enamel lesions to arrest or reverse 11. Enamel-based thresholds for surgical treatment have become more of an issue as recent attention to risk assessment and development of diagnostic systems focus more attention on enamel lesions, alternatives to surgical treatment are shown to be effective,12,13 and long-term consequences of surgical treatment are considered 14,15,16,17,18…”
Section: Introductionmentioning
confidence: 99%